Hirschsprung's Associated Enterocolitis (HAEC) Personalized Treatment with Probiotics Based on Gene Sequencing Analysis of the Fecal Microbiome. (14th October 2018) - Singer, Georg; Kashofer, Karl; Castellani, Christoph; Till, Holger
Abstract : Approximately 40% of children with Hirschsprung's disease (HD) suffer from Hirschsprung's associated enterocolitis (HAEC) despite correct surgery. Disturbances of the intestinal microbiome may play a role. Treatment with probiotics based on individual analyses of the fecal microbiome has not been published for HD patients with recurrent HAEC yet. A boy with trisomy 21 received transanal pull-through at the age of 6 months for rectosigmoid HD. With four years, he suffered from recurrent episodes of HAEC. The fecal microbiome was measured during three healthy and three HAEC episodes by next-generation sequencing. The patient was started on daily probiotics for 3 months; the fecal microbiome was measured weekly. The fecal microbiome differed significantly between healthy and HAEC episodes. HAEC episodes were associated with significant decreases of Actinobacteria and significant increases of Bacteroidetes and Proteobacteria. Probiotic treatment led to a significant increase of alpha diversity and a significant increase of Bifidobacterium and Streptococcus as well as decreases of Rikenellaceae, Pseudobutyrivibrio, Blautia, and Lachnospiraceae . A longitudinal observation of the microbiome has never been performed following correction of Hirschsprung's disease. Probiotic treatment significantly changed the fecal microbiome; the alterations were not limited to strains contained in the administered probiotics.